A Clinico Microbiological Profile of Diabetic Foot Patients (Medico Legal Update, 2021)
Introduction: Diabetic foot syndrome (DFS), a complex disorder, affects diabetics. It is the unique anatomyof the foot that leads to potentially serious infection. Three cardinal aetiological factors that predisposeto diabetic foot ulcers are ischaemia, neuropathy and infection. DFUs are challenging to cure as oftenthe diagnosis is delayed; there is presence of ischaemia, infection with multidrug-resistant organism andextension of infection to the bones. This study was conducted with the aim to determine the clinical andmicrobiological profile of diabetic foot patients and to assess their outcome.Methodology: Sixty five male and female patients of 18 and above age that presented with diabetic footulcers were enrolled over a period of 18 months.Results: Of the 65 patients enrolled, 70.77% (n=46) were males while 29.23% (n=19) were females. Maleto female ratio was 2.4:1. Diabetic foot ulcers are common in elderly population. Most commonly seen inthe age group of 51 to 60 years. When we evaluated the Wagner grade of the ulcers, it was observed thatmajority of the patients had Wagner grade III ulcer (44.62%) followed by grade II ulcer in 24.62% of thepatients. None of the patients enrolled in the present study had wagner grade I ulcer. When the risk factorspresence was evaluated in the patients, 63.08% patient had suffered trauma, this was followed by peripheralneuropathy which was present in 60.00% patients. Among the patient enrolled, 36.92% were smokers.63.08% patients had diabetes for more than 10years while 20% had diabetes of 5-10 years duration andonly 16.92% patients had diabetes of less than 5 years. We observed that USG showed presence peripheralvascular disease in 41.54% patients, which is considerably high. In the present study X-ray showed presenceof Charcot’s joint, osteomyelitis, fracture and osteoporosis in 10.77%, 24.62%, 3.08% and 4.62% patientsrespectively. We observed that in our study, anemia was present in large proportion of patients, 67.69%, inthe present study. In the present study, ulcer was managed conservatively in 38.46% of the patients. I & Dwas performed in 35.38% of the patients. While amputation was performed in 12.31% of the patients. Inthe present study, the following organisms were isolated: Staphylococcus aureus, Pseudomonas Aeruginosa,Klebsiella pneumonia, Streptococcus pyogenes and Proteus Mirabilis were present in 36.92%, 9.23%,13.85%, 18.46% and 10.77% patients, respectively. Thus the most common isolate was Staphylococcus aureus followed by Klebsiella pneumonia. Weobserved that 50% staphylococcus aureusisolates were resistant to methicillin, that ismethicillin resistant staphylococcus aureus.However, the isolated staphylococcus didnot demonstrate resistance to vancomycin orlinezolid. Gram negative organisms showedno resistance to Piperacillin+tazobactum,Imipenem and Meropenem in the present study. Amputation was performed in all the patients with Wagnergrade IV and V ulcers, while it occurred in 48.15% patients with vasculopathy and 33.33% patients withneuropathy. It was also observed that in those patients with proteus infection, amputation had to be performedin 100% patients.Conclusion: Diabetic foot ulcers pose a significant burden on the patients and on the health care system. Thecost of disability, loss of work and lower extremity amputation extends beyond the economic impact, withregards to patient quality of life.Proper management of diabetic infections requires appropriate antibiotic selection based on culture andantimicrobial susceptibility results; however, initial management comprises empirical antimicrobial therapy,which is often based on susceptibility data extrapolated from studies performed on general clinical isolates.